Vesicoovarian Fistula on an Endometriosis Abscessed Cyst - C. Tran; M. Even; M. Carbonnel; F. Preaux; F. Isnard; A. Rault; M. Rouanne; J. M. Ayoubi (Case Reports in Obstetrics and Gynecology)
We report the case of a patient who developed a vesicoovarian fistula on an endometriosis abscessed cyst. The patient presented with an advanced endometriosis stage IV complicated with a right ovarian abscessed cyst of 10 cm. A first coelioscopy with cystectomy was realized. After surgery, a voiding cystography highlighted a fistula between the ovarian abscess and the bladder. A second surgery by median laparotomy was realized with the resection of the right ovarian abscess and the resection of vesical fistula.